2016
DOI: 10.1159/000446586
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mitochondrial Disease and Secondary Mitochondrial Dysfunction: Importance of Distinction for Diagnosis and Treatment

Abstract: Mitochondrial disease refers to a heterogeneous group of disorders resulting in defective cellular energy production due to abnormal oxidative phosphorylation (oxphos). Primary mitochondrial disease (PMD) is diagnosed clinically and ideally, but not always, confirmed by a known or indisputably pathogenic mitochondrial DNA (mtDNA) or nuclear DNA (nDNA) mutation. The PMD genes either encode oxphos proteins directly or they affect oxphos function by impacting production of the complex machinery needed to run the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
162
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(181 citation statements)
references
References 132 publications
0
162
0
6
Order By: Relevance
“…Interestingly mitochondrial dysfunction does not appear to have a clear genetic basis in ASD [46]. Folate is essential for mitochondrial function [25,65], raising the possibility that insufficiency of folate could account for mitochondrial abnormalities. Others have recently suggested that folate abnormalities and ASD may be connected through other metabolic pathways that are commonly abnormal to both such as serine, lysine and/or purine metabolism [66].…”
Section: Future Perspectivementioning
confidence: 99%
“…Interestingly mitochondrial dysfunction does not appear to have a clear genetic basis in ASD [46]. Folate is essential for mitochondrial function [25,65], raising the possibility that insufficiency of folate could account for mitochondrial abnormalities. Others have recently suggested that folate abnormalities and ASD may be connected through other metabolic pathways that are commonly abnormal to both such as serine, lysine and/or purine metabolism [66].…”
Section: Future Perspectivementioning
confidence: 99%
“…Approximately 15% (DiMauro and Schon 2003) of mitochondrial disorders are caused by inherited germline mutations in the mtDNA. Mitochondrial disorders can also be caused by mutations in over 250 nDNA genes and dysfunction can be acquired due to adverse environmental effects of drugs and infections (Niyazov 2016 Marked variability remains in the diagnostic approaches, treatment, and management of mitochondrial diseases (Parikh et al 2015). Conducting large-scale clinical trials for patients with mitochondrial diseases is difficult, given their extreme clinical variability, biochemical and genetic heterogeneity, and the rarity of each etiology or subtype.…”
Section: Brief Description Of Mitochondrial Diseasesmentioning
confidence: 99%
“…У свою чергу Са 2+ -перевантаження мітохондрій та гіперпродукція АФК органелами лежать в основі розвитку таких патологічних станів, як серцево-судинні [52][53][54][55], нейродегенеративні [56][57][58], запальні захворювання [59,60], рак [61][62][63]. Саме тому перспективним напрям-ком у лікуванні вищезазначених патологій є мітохондріально-спрямована антиоксидантна терапія із використанням пластохінону, коензиму Q10, його аналога мітохінону, L-кар нітину -сполук, які здатні відносно спе цифічно акумулюватися мітохондріями і чини ти в цих компартментах антиоксидантну дію [56].…”
Section: трансмембранний обмін са 2+ в мітохондріях за патологіїunclassified
“…По-рушення транспорту Са 2+ мітохондріями та надмірне утворення в них АФК має вирішальне значення при ішемії-реперфузії та при кардіоміопатіях. Мітохондріальні кардіоміопатії можуть мати важкі прояви, включаючи серцеву недостатність, аритмію і раптову зупинку серця [52,53,56].…”
Section: трансмембранний обмін са 2+ в мітохондріях за патологіїunclassified